Relationship between Humans and Education based on the Perspective of Syed Muhammad Naquib Al-Attas - Abdullah, Agil Husain (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
Humans are superior and better creatures than other creatures of Allah Ta'ala, and humans are the only creatures that can be educated. This study aims to analyze the relationship between humans and education based on the perspective of Syed Muhammad Naquib al-Attas's thoughts. This study uses a qualitative approach with a literature study method through a review of relevant literature regarding Al-Attas's thoughts regarding the nature of humans, the nature of education, and the relationship between humans and education. While many studies explore Al-Attas' thoughts, most focus on Al-Attas' view on human being and education in general. However, little research examines Al-Attas' view on direct impact of education on humans. This study addresses this gap by investigating the relationship between humans and education, offering new insights into the positive impact of education on humans. The results of this study indicate that based on Al-Attas's perspective, humans have a dual nature and the potential for reflection and intelligence that make them special creatures. Al-Attas argues that the concept of ta'dib is the most appropriate concept for education. The relationship between humans and education from Al-Attas's perspective can be described into three points. First, education strengthens the dual nature of humans. Second, education leads humans to the purpose of their creation. Third, education improves the social order. The findings of this study highlight several areas requiring further attention, leading to the following recommendation for both future research and practical application; Future research should explore Al-Attas’ view on the concept of humanity education, and the findings should be applied on education system.